Self Branding of Grobogan District Through Mapping Superior Potential - Astuti, Tri Marhaeni Pudji; Banowati, Eva; Wijaya, Atika; Fajar, Fajar (Universitas Negeri Semarang, 2023)
Grobogan is one of the largest districts in Central Java which has various areasSelf Branding and sstereotype-its. One of the interesting expressions that seems to betagline is